Fluorescence imaging-assisted thoracoscopic anatomical lesion resection in treating congenital lung malformation - Taozhen He; Xiaoyan Sun; Guowei Che; Dengke Luo; Miao Yuan; Gang Yang; Kaisheng Cheng; Chang Xu (Scientific Reports)
Abstract Identification of lesion demarcation during thoracoscopic anatomical lesion resection is fundamental for treating children with congenital lung malformation. Existing lesion demarcations do not always meet the needs of clinical practice. This study aimed to explore the safety and efficacy of near-infrared fluorescence imaging with nebulized inhalation of indocyanine green for thoracoscopic anatomical lesion resection in children with congenital lung malformation. Under the fluorescence scope, the area of uniform green fluorescence was produced when indocyanine green was distributed into normal lung tissue, and lesions showed little or no green fluorescence, thus delineating a clear fluorescent lesion demarcation. Under the guidance of fluorescent demarcation, all the patients except one case of extralobar sequestration underwent thoracoscopic anatomical lesion resection successfully.